Transformasi Tata Kelola Wisata Bahari melalui Penguatan Destinasi dan Pemasaran Digital di Kabupaten Bone - Andi Muhammad Romi (Departemen Ilmu Pemerintahan Fisip Unhas, 2023)
Marine tourism is a strategic sector with significant potential to stimulate regional economic growth, improve community welfare, and enhance the competitiveness of tourism destinations. Bone Regency, as one of the coastal regions in South Sulawesi Province, possesses various marine tourism resources that require adaptive and innovative governance to maximize their potential. This study aims to analyze the transformation of marine tourism governance in Bone Regency, focusing on marine tourism destination development and digital-based tourism marketing. The research employed a qualitative approach with a descriptive-analytical research design. Data were collected through interviews, observations, and documentation involving the Bone Regency Tourism Office, tourism destination managers, Tourism Awareness Groups (Pokdarwis), tourism business actors, and coastal communities. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that the Bone Regency Government has transformed marine tourism governance through the development of supporting infrastructure, improvement of tourism facilities, community empowerment, and the strengthening of Tourism Awareness Groups in destination management. Furthermore, digital tourism marketing has been implemented through the utilization of social media, websites, and other digital platforms to broaden destination promotion.